Tinjauan Fiqh Muamalah pada Praktik Kerjasama dalam Pengelolaan Penjualan Mobil di RG Motor Showroom - Deryalfi Fathudin; Sandy Rizki; Nanik Eprianti (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Mudharabah is a business cooperation agreement between two parties where the first party (shahibul mal) provides all the capital, while the other party becomes the manager. One example in business is the practice of cooperation in managing car sales at the RG motor showroom, in this transaction there is a problem that the showroom uses some of the money from investors to buy other cars without the knowledge of investors. The purpose of this study was to determine the practice of cooperation in the management of car sales at the RG motor showroom and to determine the fiqh of muamalah in the practice of cooperation in the management of car sales. This study uses a qualitative method with a descriptive qualitative approach with the type of field research. Data collection techniques used are interviews, observation, and literature study. The results of this study indicate that the showroom uses some of the investor's money without permission and this is contrary to the DSN MUI fatwa no. 115/DSN-MUI/IX/2017, it can be said that this mudharabah contract is a fasid. Abstrak. Mudharabah adalah akad kerjasama usaha antara dua pihak dimana pihak pertama (shahibul mal) menyediakan seluruh modal, sedangkan pihak lainnya menjadi pengelola. Salah satu contoh dalam bisnis ialah praktik kerjasama dalam pengelolaan penjualan mobil di RG motor showroom, pada transaksi tersebut ditemui masalah bahwa pihak showroom menggunakan sebagian uang dari pemodal untuk pembelian mobil lain tanpa sepengetahuan pemodal. Tujuan penelitian ini ialah untuk mengetahui praktik kerjasama dalam pengelolaan penjualan mobil di RG motor showroom dan mengetahui fiqh muamalah pada praktik kerjasama dalam pengelolaan penjualan mobil. Penelitian ini menggunakan metode kualitatif dengan pendekatan kualitatif deskriptif dengan jenis penelitian lapangan. Teknik pengumpulan data yang digunakan ialah wawancara, observasi, dan studi pustaka. Hasil penelitian ini menunjukan bahwa pihak showroom menggunakan sebagian uang pemodal tanpa izin dan ini bertentangan dengan fatwa DSN MUI no. 115/DSN-MUI/IX/2017, maka bisa dikatakan akad mudharabah ini adalah fasid.